2019
DOI: 10.1093/jac/dkz221
|View full text |Cite
|
Sign up to set email alerts
|

Improving antibacterial prescribing safety in the management of COPD exacerbations: systematic review of observational and clinical studies on potential drug interactions associated with frequently prescribed antibacterials among COPD patients

Abstract: BackgroundGuidelines advise the use of antibacterials (ABs) in the management of COPD exacerbations. COPD patients often have multiple comorbidities, such as diabetes mellitus and cardiac diseases, leading to polypharmacy. Consequently, drug–drug interactions (DDIs) may frequently occur, and may cause serious adverse events and treatment failure.Objectives(i) To review DDIs related to frequently prescribed ABs among COPD patients from observational and clinical studies. (ii) To improve AB prescribing safety in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 220 publications
(128 reference statements)
0
5
1
1
Order By: Relevance
“…Patients with COPD are considered a high-risk population with high prevalence of smoking and relatively older age, making these persons more susceptible for possible ADEs. 17 45 Of note, in our study, we did not observe an increased risk of overall NPAEs among patients with COPD using varenicline in both the psychiatric and non-psychiatric cohorts. Of note, regarding the occurrence of specific NPAEs, less anxiety was seen in the varenicline group than in the NRT group in both cohorts.…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…Patients with COPD are considered a high-risk population with high prevalence of smoking and relatively older age, making these persons more susceptible for possible ADEs. 17 45 Of note, in our study, we did not observe an increased risk of overall NPAEs among patients with COPD using varenicline in both the psychiatric and non-psychiatric cohorts. Of note, regarding the occurrence of specific NPAEs, less anxiety was seen in the varenicline group than in the NRT group in both cohorts.…”
Section: Discussioncontrasting
confidence: 39%
“…16 Importantly, COPD patients are older and suffer from many comorbidities making these patients more susceptible to drug-drug interactions potentially leading to related adverse drug events (ADEs). 17 Similarly, it has been reported that individuals with psychiatric disorders are prone to experience relapse of psychiatric symptoms. 18 19 Although many RCTs and post hoc analyses of some RCTs showed consistent results about varenicline safety in subjects with specific psychiatric disorder, [20][21][22][23][24][25][26][27] real-world varenicline safety among these high-risk population is only explored in few studies, 28 29 several related large observational studies of high-quality were all about general population, rather than specific high-risk population.…”
Section: Introductionmentioning
confidence: 96%
“…The need to add an antibiotic to regular medications taken for the management of a chronic illness may make the choice of antibiotic more challenging, given the risk of drug interactions; this complexity is likely to increase with the number of diseases. 17 Indeed, in another study on the treatment of urinary tract infections, the cumulation of chronic diseases in an individual increased the risk of receiving a noncompliant prescription by up to 12% for patients with 4 chronic conditions. 18 In these cases, not following guidelines can be the appropriate line of conduct to prevent drug interactions, but resources should be available to support primary care physicians.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, antibiotics should be prescribed if there is consolidation on a chest radiograph or clinical signs of pneumonia, even without purulent sputum. Moreover, as COPD outpatients are mostly elderly and have lots of comorbidities, the polypharmacy may be very often and could lead to the antibiotic-related drug-drug interactions, which should be noticed while clinicians use antibiotics for AECOPD treatment [39].…”
Section: Discussionmentioning
confidence: 99%